Associations of Lower Extremity Peripheral Nerve Impairment and Risk of Dementia in Black and White Older Adults. (3rd May 2022) - Brenowitz, Willa D.; Robbins, Nathaniel M.; Strotmeyer, Elsa S.; Yaffe, Kristine
Abstract : Background and Objectives: Peripheral nerve impairments and dementia are common among older adults and share risk factors. However, few studies have examined whether peripheral nerve function and dementia are associated. We evaluated whether lower extremity peripheral nerve impairments were associated with higher incidence of dementia and whether associations differed by comorbidity subgroups (diabetes, low vitamin B12, and APOE ε4 allele carriers). Methods: We studied Black and White Health, Aging, and Body Composition Study participants 70 to 79 years of age and without dementia at enrollment. Lower extremity sensory and motor peripheral nerve function was measured at year 4 (the analytic baseline of this study). Sensory nerve impairments were measured with monofilament (1.4 g, 10 g) and vibration threshold of the toe. Monofilament insensitivity was defined as unable to detect monofilament (3 of 4 touches), and vibration detection impairment was defined as >130 μm. Fibular motor impairments were defined as <1 mV compound motor action potential (CMAP) amplitude and slow nerve conduction velocity <40 m/s. Incident dementia over the following 11 years was determined from medical records, cognitive scores, and medications. Cox proportional hazard models adjusted for demographics and health conditions assessed associations of nerve impairments with incident dementia. Results: Among 2, 174 participants (52% women, 35% Black), 45% could not detect monofilament 1.4 g, 9% could not detect monofilament 10 g, 6% could not feel vibration, 10% had low CMAP amplitude, and 24% had slow conduction velocity. Monofilament 10 g (hazard ratio [HR] 1.35, 95% CI 0.99–1.84) and vibration detection insensitivity (HR 1.73, 95% CI 1.24–2.40) were associated/borderline associated with a higher risk of dementia after covariate adjustment. Estimates were elevated but not significant for monofilament 1.4 g, CMAP amplitude, and conduction velocity ( p > 0.05). Increasing number of peripheral nerve impairments was associated with higher risk of dementia in a graded fashion; for ≥3 impairments, the HR was 2.37 (95% CI 1.29–4.38). In subgroup analyses, effect estimates were generally higher among those with diabetes, low vitamin B12, and APOE ε4 allele except for vibration detection. Discussion: Peripheral nerve impairments, especially sensory, were associated with a higher risk of dementia even after adjustment for age and other health factors. These associations may represent a shared susceptibility to nervous system degeneration.